FABP4 in Paneth cells regulates antimicrobial protein expression to reprogram gut microbiota - Xiaomin Su; Mengli Jin; Chen Xu; Yunhuan Gao; Yazheng Yang; Houbao Qi; Qianjing Zhang; Xiaorong Yang; Wang Ya; Yuan Zhang; Rongcun Yang (Gut Microbes)
Antimicrobial proteins possess a broad spectrum of bactericidal activity and play an important role in shaping the composition of gut microbiota, which is related to multiple diseases such as metabolic syndrome. However, it is incompletely known for the regulation of defensin expression in the gut Paneth cells. Here, we found that FABP4 in the Paneth cells of gut epithelial cells and organoids can downregulate the expression of defensins. FABP4fl/flpvillinCreT mice were highly resistance to Salmonella Typhimurium (S.T) infection and had increased bactericidal ability to pathogens. The FABP4-mediated downregulation of defensins is through degrading PPARγ after K48 ubiquitination. We also demonstrate that high-fat diet (HFD)-mediated downregulation of defensins is through inducing a robust FABP4 in Paneth cells. Firmicutes/Bacteroidetes (F/B) ratio in FABP4fl/flpvillinCreT mice is lower than control mice, which is opposite to that in mice fed HFD, indicating that FABP4 in the Paneth cells could reprogram gut microbiota. Interestingly, FABP4-mediated downregulation of defensins in Paneth cells not only happens in mice but also in human. A better understanding of the regulation of defensins, especially HFD-mediated downregulation of defensin in Paneth cells will provide insights into factor(s) underlying modern diseases.Abbreviations: FABP4: Fatty acid binding protein 4; S. T: Salmonella Typhimurium; HFD: High-fat diet; Defa: α-defensin; 930 HD5: Human α-defensin 5; HD6: Human α-defensin 6; F/B: Firmicutes/Bacteroidetes; SFB: Segmental filamentous bacteria; AMPs: Antimicrobial peptides; PPARγ: Peroxisome proliferator-activated receptor γ; P-PPAR: Phosphorylated PPAR; Dhx15: DEAD-box helicase 15; 935 EGF: Epidermal growth factor; ENR: Noggin and R-spondin 1; CFU: Colony forming unit; Lyz1: Lysozyme 1; Saa1: Serum amyoid A 1; Pla2g2a: Phospholipase A2, group IIA; MMP-7: Matrix metalloproteinase; AU-PAGE: Acid-urea polyacrylamide gel electrophoresis; PA: Palmitic 940 acid; GPR40: G-protein-coupled receptor; GF: Germ-free; EGF: Epidermal growth factor; LP: Lamina propria; KO: Knock out; WT: Wild-type.